Genetic and pharmacological inhibition of inflammasomes reduces the survival of Mycobacterium tuberculosis strains in macrophages - Subbarao, Sathyavani (Sci Rep, 2020)
Mycobacterium tuberculosis infection causes high rates of morbidity and mortality. Host-directed therapy may enhance the immune response, reduce tissue damage and shorten treatment duration. The inflammasome is integral to innate immune responses but over-activation has been described in tuberculosis (TB) pathology and TB-immune reconstitution syndrome. Here we explore how clinical isolates differentially activate the inflammasome and how inflammasome inhibition can lead to enhanced bacterial clearance. Wild-type, Nlrp3(−/−)/Aim2(−/−), Casp1/11(−/−) and Asc(−/−) murine bone-marrow derived macrophages (BMDMs) were infected with laboratory strain M. tuberculosis H37Rv or clinical isolates from various lineages. Inflammasome activation and bacterial numbers were measured, and pharmacological inhibition of NLRP3 was achieved using MCC950. Clinical isolates of M. tuberculosis differed in their ability to activate inflammasomes. Beijing isolates had contrasting effects on IL-1β and caspase-1 activation, but all clinical isolates induced lower IL-1β release than H37Rv. Our studies suggest the involvement of NLRP3, AIM2 and an additional unknown sensor in IL-1β maturation. Pharmacological blockade of NLRP3 with MCC950 reduced bacterial survival, and combined treatment with the antimycobacterial drug rifampicin enhanced the effect. Modulating the inflammasome is an attractive adjunct to current anti-mycobacterial therapy that warrants further investigation.